1981
DOI: 10.1021/ed058p686
|View full text |Cite
|
Sign up to set email alerts
|

Teaching introductory chemistry: Generality of the PSI approach

Abstract: A formal, comprehensive evaluation of the personalized system of instruction was conducted in an introductory course. The results were promising and encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…A PSI, also known as the Keller Plan, grew in popularity in the 1970s throughout science classrooms. Classrooms that implemented a PSI saw positive effects on student learning, and the method was favorably received by students. However, during the 1980s, interest in PSI decreased, a major reason being the substantial time commitment required to maintain a PSI coursetracking student progress and grading multiple assessments. Because of the overwhelming positive outcomes observed when using a PSI in chemistry courses, I decided to revitalize this type of instruction for organic chemistry with modern technology and use of a learning management system (LMS). With access to these newer technological tools, grading can be automated, questions can be randomized for multiple iterations of assessment, , student progress can be easily tracked, lecture material can be customized, and content can be organized with completion requirements to progress to new material.…”
Section: Introductionmentioning
confidence: 99%
“…A PSI, also known as the Keller Plan, grew in popularity in the 1970s throughout science classrooms. Classrooms that implemented a PSI saw positive effects on student learning, and the method was favorably received by students. However, during the 1980s, interest in PSI decreased, a major reason being the substantial time commitment required to maintain a PSI coursetracking student progress and grading multiple assessments. Because of the overwhelming positive outcomes observed when using a PSI in chemistry courses, I decided to revitalize this type of instruction for organic chemistry with modern technology and use of a learning management system (LMS). With access to these newer technological tools, grading can be automated, questions can be randomized for multiple iterations of assessment, , student progress can be easily tracked, lecture material can be customized, and content can be organized with completion requirements to progress to new material.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of various attempts to make teaching and learning more adaptive can be found in both the early and current research literature. They include, though not limited to, mastery learning (e.g., Bloom, 1968), Personalized Systems of Instruction or PSI (e.g., Keller, 1968; Gifford & Vicks, 1982; Davies, 1981), assorted forms of peer instruction (e.g., Mazur, 1997), various reciprocal reading/writing activities (e.g., Huang & Yang, 2015; MacArthur, Schwartz & Graham, 1991), adaptive hypermedia (Brusilovsky, 2001), accommodation for individual learning styles (e.g., Özyurt & Özyurt, 2015) and more recent Intelligent Tutoring Systems or ITS (e.g., Huang & Shiu, 2012; VanLehn, 2011). To some extent, findings of primary research on these and related instructional practices have been summarized in two rather sparse collections of meta‐analyses separated in time by almost three decades.…”
Section: Introductionmentioning
confidence: 99%
“…It differs from the Keller plan in the question of pacing: students must, complete five of the 16 units by the end of the sixth week (of ten) of instruction. Such instructor-pacing (5)(6)(7) was added to the course early in its development when it was observed that students at complete liberty to set their rate of progress failed in disturbing numbers to set any pace at all. Students not meeting the deadline are dropped from the course.…”
mentioning
confidence: 99%